Distribution and accumulation of perfluororinated chemicals (PFCs) in water and sediment in two urban large lakes, Hanoi - Anh, Duong Hong (VNU Journal of Science: Natural Sciences and Technology, 2018)
The perfluororinated chemicals (PFCs) were determined in 40 surface water samples anf 36 sediment samples which were collected in two large urban lakes of Hanoi that are West lake and Yen So lake in rainy and dry seasons. Concentrations of  total analysed PFCs was averaged of 10.78ng/L (8.13 – 13.25 ng/L) in water of West lake and  14.55 ng/L (12.42 – 17.64 ng/L) in water of Yen So lake, respectively. The average amount of PFCs in sediment of West lake was 0.11 ng/g dry sample (0.03-0.26 ng/g dry sediment)  and  PFCs of Yen So lake was  0.79 ng/g dry sample (0.08-2.01 ng/g dry sediment). The dominant PFCs with short cabon chain of PFC moleculars that were found a range of  C4 to C10 for water and a range of C8 to C10 for sediment in two  lakes.  PFCs accumulation was recognized in sediment and water of both lakes Yen So and West lake with distribution factor (log K D ) in a range of 1.05 and 2.91.